From the post-industrial prophecy to the de-industrial nightmare: Stagnation, the manufacturing fetish and the limits of capitalist wealth. (October 2022) - Moraitis, Alexis
The post-2008 era saw a return of the manufacturing fetish, the idea that manufacturing constitutes the flywheel of growth without which no nation can thrive. Across the Global North and South, voices are calling to reverse deindustrialization and revive manufacturing. While today deindustrialization is met with anxiety, in the 1930s economists predicted deindustrialization but interpreted it as a liberating process leading to a post-industrial age based on material abundance and widespread economic security. Far from delivering this vision, deindustrialization actually produces a precarious economic order driven by labour precarity, economic stagnation and lost development opportunities for the Global South. What can be termed the Baumolian and Kaldorian frameworks, attribute this precarious reality to services' inability to replace manufacturing as a growth engine given their technologically stagnant nature. However, this article argues that, by focusing on the technical aspects of service economies, such views overlook the social limits of the capitalist economy and its historically specific conception of wealth, value. As capitalism matures, productivity becomes an increasingly inadequate form of augmenting social wealth as it results in great increases in physical output but counterintuitively undermines the expansion of value. Capitalism is underpinned by a secular movement towards declining dynamism, as it increasingly struggles to maintain its former economic vigour. Stagnation and heightened labour precarity are not merely the product of tertiarization but symptoms of capitalism's declining trajectory.